The utilization of the concept of profession to understand social problems: sharing preliminary results from systematic review - Wildschut, Angelique; Mbatha, Nomkhosi A.; Meyer, Tamlynne (Frontiers in Sociology, 2025)
The nature of work has experienced steady shifts that have accelerated over the last three decades, raising important sociological questions; for instance, what does this mean for individuals and groups, and their relation to society, markets and the political systems that contextualize attempts and opportunities for different forms of livelihood? The concept of profession has been a key construct for sociological analysis to understand, study and theorise the implications of such shifts in different countries, workplaces and even particular occupational groups. Studies of professions have thus contributed to knowledge in many ways, not only by highlighting the implications for individuals and groups within work contexts but also illustrating importantly how this relates or not to wider societal phenomena. However, there are strong contentions that because its function as a mechanism of social structure formation has weakened significantly over time, as a sociological category and construct, the concept of profession is no longer relevant in contemporary times. This paper shares preliminary results from a systematic review of literature on the application and conceptualisation of the term profession between 2022 and 2023 to start engaging with the question of whether it has exhausted its sociological relevance. The findings suggest firstly that while there has been an overall decline in the utilization of profession-related terms, a slight increase in the utilization of profession is apparent. Secondly, in the reviewed papers, limited engagement with the conceptual underpinning of the construct exists. Finally, while critical engagement with the concept is not always apparent, most papers recognize a clear link between social phenomena and the role of the profession/s toward maintaining or dismantling such challenges in society.